2022
DOI: 10.3390/polym14030387
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study on Extraction of Cellulose Fiber from Rice Straw Waste from Chemo-Mechanical and Pulping Method

Abstract: Inspired by nature, cellulose extracted from plant wastes has been explored, due to its great potential as an alternative for synthetic fiber and filler that contributes to structural performance. The drive of this study was to extract, treat, and evaluate the characteristics of rice straw (RS) (Oryza sativa L.) cellulose as a biodegradable reinforcement to be utilized in polymer base materials. Two routes of extraction and treatment were performed via the pulping (Route 1) and chemo-mechanical methods (Route … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(18 citation statements)
references
References 68 publications
2
16
0
Order By: Relevance
“…The Similar narrower band was observed in the extracted sample at 3332cm -1 of H-bonded OH groups and at 2901 cm -1 to the C-H stretching on the work done by [10], in Retama retama stems. The cellulose extraction from rice straw waste showed that the broad band was seen between 3600-3100 cm -1 and 2912 cm -1 which is associated to O-H stretching of hydrogen bond and CH 2 stretching vibration respectively; these bands show the distinguishing features of cellulose which was seen in this work as well [19]. Similarly of cellulose characterization of Calotropis procera on the CPF, peaks at 1163 cm -1 and 899 cm -1 were related to hemicellulose's C-O stretching and C-H vibrations, respectively [23].…”
Section: Structural Characterizationsupporting
confidence: 78%
“…The Similar narrower band was observed in the extracted sample at 3332cm -1 of H-bonded OH groups and at 2901 cm -1 to the C-H stretching on the work done by [10], in Retama retama stems. The cellulose extraction from rice straw waste showed that the broad band was seen between 3600-3100 cm -1 and 2912 cm -1 which is associated to O-H stretching of hydrogen bond and CH 2 stretching vibration respectively; these bands show the distinguishing features of cellulose which was seen in this work as well [19]. Similarly of cellulose characterization of Calotropis procera on the CPF, peaks at 1163 cm -1 and 899 cm -1 were related to hemicellulose's C-O stretching and C-H vibrations, respectively [23].…”
Section: Structural Characterizationsupporting
confidence: 78%
“…Plant fibers have been applied since the industrialization era. Humans have utilized it for over 40,000 years for its advantages [40]. Apart from being the most dominant biopolymer on the planet, it also offers a variety of exciting characteristics, for example, excellent biocompatibility, lower density, substantial strength, and most beneficial mechanical properties at a lower cost.…”
Section: Nanocellulose From Plant Fibermentioning
confidence: 99%
“…These properties have been reportedly associated with their type, origin, and age. The important constituent of the plant fibers is cellulose, hemicellulose, and lignin [40]. Structurally, plant cell walls are cytoplasmic matrices made of secondary walls that are enclosed within the primary walls forming an integral part of the plant structure.…”
Section: Nanocellulose From Plant Fibermentioning
confidence: 99%
“…Cellulose is a great and widespread type of renewable resource in nature, found in straw and textile waste [ 1 ]. The degraded products can be used to produce biofuels or energy for other organisms, which is of great significance to industry and nutrient cycling [ 2 ].…”
Section: Introductionmentioning
confidence: 99%